Pengaruh Dewan Komisaris, Kepemilikan Manajerial dan Komite Audit terhadap Manajemen Laba pada Perusahaan Bumn di Bursa Efek Indonesia Periode Tahun 2011-2015 - Gunawan Gunawan; Elona Meita Situmorang (Jurnal Ekonomi, Manajemen dan Perbankan (Journal of Economics, Management and Banking), 2016)
The research aims to get analyze the effect od board of independent commissioners, managerial ownership, and the audit committee to earnings management at state-owned companies listed on the Indonesia Stock Exchange from 2011 until 2015. The independent variables in this research are boards of independent commissioners by the proportions between boards of independent commissioners and the numbers of commissioners boards, managerial ownership which measured by the numbers of stock owned by management, and the audit committee which measured by comparison between independent audit committee and the numbers of audit committee in the company. This research has been analyzed using Eviews 7 program, for panel Data Regression. The result of this research shows that board independent commissioners have a negative impact on earnings management. Meanwhile, managerial ownership and audit committee doesn’t have an impact on earnings management.